Analisis Pertumbuhan Aset Dan Struktur Modal Terhadap Profitabilitas Pada PT. Penjaminan Kredit Daerah Nusa Tenggara Timur - Sesylia Rambu Prayng; Nikson Tameno; Cicilia Apriliana Tungga (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
The purpose of this study is to analyze the knowledge that affects Assets and Profitability at PT. JAMKRIDA NTT and to analyze the effect of capital deposits on profitability at PT. JAMKRIDA NTT. This study uses a qualitative descriptive method, using a research method that focuses on in-depth observation to understand the phenomena that occur, this approach uses descriptive data in the form of discussions and writings or oral from people and actors who want to be interviewed while quantitative research focuses on data and statistics to measure, calculate and compare from the data taken such as analyzing data from asset growth and the company's capital structure and how the company's profitability is. The results of this study are that asset growth and capital structure affect profitability at a The company has a very important influence in running a company's activities, especially to increase the value of the company.